2016
DOI: 10.1186/s12939-016-0473-y
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in the use of maternal and child health services in the Philippines: do pro-poor health policies result in more equitable use of services?

Abstract: BackgroundThe Philippines failed to achieve its Millennium Development Goal (MDG) commitment to reduce maternal deaths by three quarters. This, together with the recently launched Sustainable Development Goals (SDGs), reinforces the need for the country to keep up in improving reach of maternal and child health (MCH) services. Inequitable use of health services is a risk factor for the differences in health outcomes across socio-economic groups. This study aims to explore the extent of inequities in the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Another application of inequality analysis is tracking health inequalities over time. It helps to understand the effect of new health interventions or policy measures in terms of reducing health inequalities as well as inequities [22, 40, 41]. Sri Lankan health authorities should incorporate health inequality measures into existing health indicators to track progress over time in reducing inequalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another application of inequality analysis is tracking health inequalities over time. It helps to understand the effect of new health interventions or policy measures in terms of reducing health inequalities as well as inequities [22, 40, 41]. Sri Lankan health authorities should incorporate health inequality measures into existing health indicators to track progress over time in reducing inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…The explanatory variables used in the decomposition analysis were education level of women, ethnicity, education level of husband/partner, sector of residence, province of residence, and the wealth quintile. These covariates were selected a priori, in line with similar studies available in the literature [1922]. Also, these covariates are recognised as social determinants of health that are closely linked with both health inequalities and inequities [23].…”
Section: Methodsmentioning
confidence: 99%
“…Education level was categorized as “none” for women who had not received any kind of formal education, “primary” for women who completed primary education level, “secondary” for women who completed secondary education level, and “highest” for women who completed college and all university level; Marital status was categorized as “no spouse” for women who were single, divorced, separated or widowed and "living with spouse" for women who were married or living with a partner during the interview; Employment was categorized as "employed" for women who reported to be employed and paid in salary in terms of cash and "not employed" for those who did not have any kind of job and paid in terms of cash. The selection of these variables was based on previous studies related to socioeconomic inequalities in accessing maternal healthcare [ 19 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, women from lower socioeconomic strata are generally exposed to various types of perinatal complexities including premature birth, low birth weight, restricted growth in intra-uterine, antenatal and neonatal mortality, etc. (De Groot et al, 2019;Paredes, 2016;Zere et al, 2013).…”
Section: Incomementioning
confidence: 99%
“…Evidence from sub-Saharan Africa showed that the poor women are the worst sufferer of maternal health complexities due to out of pocket health payments (McKinnon et al, 2016;C. Zhang et al, 2019) as a result women from families having less wealth are at higher risk of death (Paredes, 2016;Rajesh Kumar Rai et al, 2012;Walton & Schbley, 2013). This is the picture of Pakistan also, along with other lower-middle-income countries in South-Asia (Mumtaz et al, 2014), besides, the study of Zere et al (2013) and Walton and Schbley (2013) demonstrated that in Bangladesh, the use of ANC is more common among women from wealthier section than the poor counterparts.…”
Section: Incomementioning
confidence: 99%